2020
DOI: 10.1101/2020.08.18.255984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arabidopsis Myosin XIK Interacts with the Exocyst Complex to Facilitate Vesicle Tethering during Exocytosis

Abstract: Myosin motors are essential players in secretory vesicle trafficking and exocytosis in yeast and mammalian cells; however, similar roles in plants remain a matter for debate, at least for diffusely-growing cells. Here, we demonstrate that Arabidopsis (Arabidopsis thaliana) myosin XIK, via its globular tail domain (GTD), participates in the vesicle tethering step of exocytosis through direct interactions with the exocyst complex. Specifically, myosin XIK GTD bound directly to the SEC5B subunit of exocyst in vit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 84 publications
3
25
0
Order By: Relevance
“…The same intra-molecular regulation in MYA2 suggests that MYA2 is not merely responsible for driving continuous cytoplasmic streaming, but also for more complex transport equipped with a recycling system. It has recently been reported that MYA2 is involved in several intracellular transports and functions, such as processing-body movement, pathogen responses, auxin responses, cell death, cell division, regulation of exocytosis, lipid body transport 18, [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…The same intra-molecular regulation in MYA2 suggests that MYA2 is not merely responsible for driving continuous cytoplasmic streaming, but also for more complex transport equipped with a recycling system. It has recently been reported that MYA2 is involved in several intracellular transports and functions, such as processing-body movement, pathogen responses, auxin responses, cell death, cell division, regulation of exocytosis, lipid body transport 18, [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, putative CSC delivery vesicles arrive in the cortical cytoplasm near the PM, display erratic local movement for several seconds, become spatially restricted in their movement and maintain a static position for 60-90s, and then undergo steady and linear movement as catalytically-active CESA complexes (see refs. [17,23,25] and Figure 1A). The pause phase is hypothesized to encompass tethering, docking, and fusion of CSC vesicles, possibly followed by the activation of CESAs before they synthesize cellulose and show linear motility.…”
Section: Introductionmentioning
confidence: 92%
“…Recent advances in high spatiotemporal resolution live-cell imaging and utilization of functional, fluorescent protein-tagged CESAs have allowed CSC trafficking to emerge as a powerful model for studying exocytosis in plant cells [17,[23][24][25]. In particular, single-particle tracking has illuminated specific steps in the exocytosis process based on the size, unique spatial localization and motility patterns of CSCs on different endomembrane compartments [17,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations